An extremely rare cause of generalized lymphadenopathy in children: Kimura's disease - Ceçen, Emre; Kaçar-Döger, Firuzan; Etensel, Barlas (The Turkish Journal of Pediatrics, 2010)
Kimura's disease, characterized by a triad of painless subcutaneous masses in the head and neck, prominent eosinophilia and markedly elevated immunoglobulin E levels, is an uncommon idiopathic, chronic inflammatory disease that usually affects young and middle-aged Asian males. Kimura's disease is known usually as a localized process and is an extremely rare cause of generalized lymphadenopathy in children. We report an eight-year-old Turkish boy with Kimura's disease who presented with generalized lymphadenopathy masquerading as malignant lymphoma.